Kedudukan Private Key Dalam Pewarisan Aset Kripto: Tantangan Pembuktian Waris Dalam Perspektif Kitab Undang-Undang Hukum Perdata - Rayi Kharisma Rajib; Fauzil Adim Mahsun; Fakhri Fakhri (JURNAL ILMIAH NUSANTARA, 2026)
This research analyzes the legal challenges of cryptocurrency inheritance in Indonesia, specifically the conflict between the principle of le mort saisit le vif in the Civil Code and the decentralized nature of blockchain based on private keys. Through a doctrinal approach, it is found that the private key functions as an essential accessory element for realizing inheritance rights, although it is not a standalone object (zaak). Technical hurdles such as blockchain pseudonymity create a gap between legal ownership and physical control of assets. This study concludes the need for legal reform through digital estate planning and specialized regulations to prevent inherited crypto assets from becoming lost assets.